Sleep patterns in 1 to 36 month-old children - Catharina Sambo; Rini Sekartini; Partini Trihono (Indonesian Pediatric Society Publishing House, 2010)
Background Better understanding about sleep patterns in Indonesian children can contribute to basic knowledge for educating parents and health providers about good sleep hygiene. Objectives To find out sleep patterns in 1􀁊36 month􀁊old children. Method A descriptive, cross􀁊sectional study was held in East Jakarta on May 2009. Subjects were 1 to 36 months old children who came \\lith their parents or primary caregivers. Data collection was performed using modified Brief Infant Sleep Questionnaire (BISQ), consisted of subjects' characteristics, sleep patterns, sleep problems, and associating factors. Results Among 147 children, sleep problems were identified in 33.3% of them. Bedtime was mostly at 8 p.m., wake up time was 5 a.m. Median time needed to fall asleep was 20 minutes. Average frequency of night waking was twice during one night. Median night waking duration was 15 minutes. Median sleep duration at night was 9 hours 20 minutes, and median nap duration was 2 hours 20 minutes. Median total sleep time was 12 hours. Prone sleeping position was significantly associated \\lith sleep problems (p􀁋0.036, RR􀁋1.67, 95%CI􀁋1.66-2.64). Conclusions Prevalence of sleep problem is 33.3%, \\lith awakening at night was being the most occurring problem. Prone sleeping position is associated \\lith sleep problems. [Paediatr Indones. 2010;50:170-5].